Ultrafast Bright Squeezed Vacuum in Nearly Single Spatio-Temporal Mode - Cusson, P.; Rasputnyi, A.; Tani, F.; Seletskiy, D.; Chekhova, M. (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We demonstrate nearly single-mode bright squeezed vacuum sources with unprecedentedly high peak power (with mean values up to tens of MW) and few-cycle durations, which enable accessing the non-perturbative regime of light-matter interaction.
CRIS-Team Scopus Importer:2024-10-25